THE TUNAICHA FORMATION AND ITS AGE ANALOGUES, SOUTHERN SAKHALIN - Zharov A.E.; Gal'versen V.G.; Serova M.Ya.; Fot'yanova L.I. (My University, 2004)
The terrigenous Tunaicha Formation overlying dislocated Mesozoic basement was recently established at the base of Cenozoic deposits in southeastern Sakhalin (the Aniva and Dolinsk districts). The formation stratotype is in the Cape Tunaicha area (Bay of Mordvinov). The formation is attributed to the terminal middle-upper Eocene based on benthic and associated sparse planktonic foraminifers and on coeval floral assemblage. The Tunaicha period corresponded to formation time of new sedimentary basins in southeastern Sakhalin and Hokkaido.
Keywords: Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен